Le codéveloppement « inter »professionnel pour aller au-delà des disciplines en formation initiale - Marie-Pierre Baron; Nathalie Sasseville; Catherine Vachon; Carole Côté; Manon Doucet (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The Clinique Universitaire d’Orthopédagogie at the Université du Québec à Chicoutimi (Quebec, Canada) allows students in teaching Special and Social Education and in Social Work to provide interprofessional services to the public and hence to develop, during their training, competencies specific to collaboration. In order to support interdisciplinary collaboration, mechanisms are implemented in courses, including the professional co-development group. The purpose of this article is to describe how the professional co-development group mechanism can support interdisciplinary collaboration work with students in initial training. Through the content analysis of group interviews conducted at the beginning and at the end of the project, it is possible to observe that, on the one hand, the training context enables the achievement of co-development objectives, and on the other hand, that professional co-development groups allow for the implementation of factors promoting the creation of the collaborative relationship. This initial training context, implemented in clinical activities, ensures to bind theory to practice and to adapt the initial training to the needs of the educational and social environments.